Evaluation of Dry Eye and Meibomian Gland Dysfunction in Teenagers with Myopia through Noninvasive Keratograph - Xiu Wang; Xiaoxiao Lu; Jun Yang; Ruihua Wei; Liyuan Yang; Shaozhen Zhao; Xilian Wang (Journal of Ophthalmology)
Purpose. This study aims to evaluate dry eye and ocular surface conditions of myopic teenagers by using questionnaire and clinical examinations. Methods. A total of 496 eyes from 248 myopic teenagers (7–18 years old) were studied. We administered Ocular Surface Disease Index (OSDI) questionnaire, slit-lamp examination, and Keratograph 5M. The patients were divided into 2 groups based on OSDI dry eye standard, and their ocular surfaces and meibomian gland conditions were evaluated. Results. The tear meniscus heights of the dry eye and normal groups were in normal range. Corneal fluorescein scores were significantly higher whereas noninvasive break-up time was dramatically shorter in the dry eye group than in the normal group. All three meibomian gland dysfunction parameters (i.e., meibomian gland orifice scores, meibomian gland secretion scores, and meibomian gland dropout scores) of the dry eye group were significantly higher than those of the normal group (P<0.0001). Conclusions. The prevalence of dry eye in myopic teenagers is 18.95%. Meibomian gland dysfunction plays an important role in dry eye in myopic teenagers. The Keratograph 5M appears to provide an effective noninvasive method for assessing ocular surface situation of myopic teenagers.